Preparation method of permanent magnetic ferrite with high performance and high breakdown voltage

By mixing the strontium ferrite pre-sintered material of different systems and recycled waste materials in proportion, and adding auxiliary materials for ball milling and sintering, a permanent magnet ferrite with high performance and high breakdown voltage is obtained, which solves the problem of low breakdown voltage of existing ferrite materials and achieves efficient magnetic and electrical performance improvements.

CN119661213AInactive Publication Date: 2025-03-21SINOSTEEL ANHUI TIANYUAN TECH

Patent Information

Application Number
CN202411797894.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing permanent magnet ferrite materials have low breakdown voltage at high voltage, resulting in a sharp increase in internal current, affecting the service life of magnetic tiles, and there is a lack of effective methods to improve the breakdown voltage of high-performance permanent magnet ferrite in China.

Method used

By mixing the 5-series strontium ferrite pre-sintered with lanthanum cobalt-free strontium ferrite pre-sintered with lanthanum cobalt-added strontium ferrite pre-sintered with lanthanum cobalt and recovered waste in a uniform proportion, adding auxiliary materials, ball milling, magnetic press forming and sintering, a high-performance, high-breakdown voltage permanent ferrite is produced.

Benefits of technology

It significantly improves the breakdown voltage of high-performance ferrite, reduces the internal current of ferrite at high voltage, and ensures magnetic performance, promotes the application of ferrite at high frequency, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177259920000041
    Figure BDA0005177259920000041
  • Figure BDA0005177259920000051
    Figure BDA0005177259920000051
  • Figure BDA0005177259920000071
    Figure BDA0005177259920000071
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance high-breakdown-voltage permanent magnetic ferrite, relates to the technical field of preparation of permanent magnetic ferrites, and aims to solve the problem that the breakdown voltage performance cannot meet the requirement when a high-performance ferrite is prepared on the basis of a 9-series strontium ferrite pre-sintering material added with lanthanum and cobalt. The preparation method comprises the following steps: uniformly mixing a lanthanum-cobalt-free 5-series strontium ferrite pre-sintered material, a lanthanum-cobalt-added 9-series strontium ferrite pre-sintered material and a recycled waste material according to a ratio to serve as raw materials, adding auxiliary materials, mixing, putting into a ball milling tank, adding water, carrying out sufficient ball milling, discharging from the tank, filtering water, magnetizing, pressurizing and forming in a pressing machine, heating and sintering a formed blank, and carrying out high-temperature sintering to obtain the lanthanum-cobalt-free strontium ferrite composite material. Grinding and drying to obtain the permanent magnetic ferrite; the process is simple, the breakdown voltage of the high-performance ferrite added with lanthanum and cobalt is greatly improved, the internal current of the ferrite under high voltage is reduced, meanwhile, the magnetic performance is ensured, and the application of the ferrite under high frequency is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permanent ferrite preparation, in particular to a method for preparing a permanent ferrite with high performance and high breakdown voltage. Background Art

[0002] In recent years, in addition to clear requirements for the magnetic properties of permanent ferrites, downstream ferrite manufacturers have also put forward new requirements for other parameters such as the electrical properties of materials. Existing ferrite materials have large currents inside the magnets under high-frequency applications, resulting in high eddy current losses, causing heating of the magnetic tiles and reducing the service life of the motor.

[0003] Permanent ferrite materials have a limit voltage under high voltage. After exceeding this voltage value, the current in the permanent ferrite material will increase sharply (from 0.1mA to more than 10mA in an instant), which is called breakdown phenomenon. This limit value is the breakdown voltage of ferrite. 3+ ions replace the divalent Sr 2+ Ions, according to the law of conservation of charge, some Fe 3+ Will be reduced to Fe 2+ , changing the magnetocrystalline anisotropy and stabilizing the magnetoplumbite structure, but Fe 3+ and Fe 2+ The energy required for electrons to transition between the two ions is small, and electrons can easily move freely between them, which leads to a significant reduction in the breakdown voltage of ferrites. However, at present, there is a blank in the research on improving the breakdown voltage of high-performance permanent ferrites in China.

[0004] At present, 9 series high-performance ferrite pre-sintered materials on the market are all added with lanthanum and cobalt, so the breakdown voltage of high-performance ferrite is very low, and its breakdown voltage is generally below 0.01kV. At 0.01kV, the current inside the ferrite can even reach tens of milliamperes, and the breakdown voltage is far lower than the current market requirements; therefore, a preparation method for high-performance and high-breakdown voltage permanent magnet ferrite is urgently needed to solve this problem. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a high-performance and high-breakdown voltage permanent ferrite to solve the problems mentioned in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-performance and high-breakdown voltage permanent magnetic ferrite, comprising the following specific contents:

[0007] The 5-series strontium ferrite pre-sintered material without lanthanum and cobalt, the 9-series strontium ferrite pre-sintered material with lanthanum and cobalt added, and the recycled waste are uniformly mixed in proportion as raw materials, and after adding auxiliary materials and mixing, they are put into a ball mill and fully ball milled with water, and the water is filtered after being taken out of the jar, and the permanent magnet ferrite is obtained by magnetizing and pressing in a press, and then the formed blank is heated and sintered, and then dried after grinding.

[0008] Among them, the recycled waste materials are grinding materials and / or defective products generated in the preparation process of strontium ferrite, and the auxiliary materials include SiO2, SrCO3, Al2O3, H3BO3, La2O3, Co3O4 and sorbitol; in the above method, sorbitol is fixedly used at 0.1% of the mass of the raw material, and the adjusted auxiliary materials include one or more of SiO2, SrCO3, Al2O3, H3BO3, La2O3 and Co3O4.

[0009] Preferably, in the raw materials, by mass percentage, the addition ratio of 9-series strontium ferrite pre-sintered material is 40-50%, the addition ratio of 5-series strontium ferrite pre-sintered material is 30-50%, and the addition ratio of recycled waste is 10-20%.

[0010] Preferably, the adjustment range of the auxiliary materials is calculated as a percentage of the raw material mass, and the amount of SiO2 is 0.02-0.15%, the amount of SrCO3 is 0.3-0.8%, the amount of Al2O3 is 0.1-0.7%, the amount of H3BO3 is 0.1-0.45%, the amount of La2O3 is 1-2.25%, and the amount of Co3O4 is 0.4-0.9%.

[0011] Preferably, the components in the recycled waste include Fe, SiO2, Al2O3, CaO, SrO, La2O3, and Co3O4.

[0012] Preferably, the raw materials are added to the auxiliary materials and mixed, and then ball milled for 8 to 12 hours.

[0013] Preferably, a roller kiln is used for sintering, and the sintering temperature is 1210±10°C.

[0014] Preferably, in the raw materials, the addition ratio of 9 series strontium ferrite pre-sintered material is 40%, the addition ratio of 5 series strontium ferrite pre-sintered material is 40%, and the addition ratio of recycled waste material is 20%; in the auxiliary materials, in terms of percentage of the mass of the raw materials, the amount of SiO2 is 0.08-0.14%, the amount of SrCO3 is 0.7-0.8%, the amount of Al2O3 is 0.1-0.3%, the amount of H3BO3 is 0.3-0.4%, the amount of La2O3 is 2.25%, and the amount of cobalt oxide is 0.9%. The permanent magnet ferrite prepared by the above method has a breakdown voltage of 4-10kV, a remanence of more than 410mT, a coercive force of more than 300kA / m, an intrinsic coercive force of more than 360kA / m, and a maximum magnetic property of 32kJ / m3 above.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] 1. The preparation method of the high-performance and high-breakdown voltage permanent ferrite greatly improves the breakdown voltage of the high-performance ferrite with added lanthanum and cobalt by compounding a variety of raw materials and adjusting specific auxiliary materials, reduces the internal current of the ferrite under high voltage, and ensures the magnetic properties at the same time, thus promoting the application of ferrite under high frequency.

[0017] 2. The preparation method of the high-performance, high-breakdown voltage permanent magnetic ferrite has a simple process, is easy to put into large-scale production, can be quickly industrialized, and at the same time reduces the production cost of the ferrite, achieving cost reduction and efficiency improvement of the ferrite. DETAILED DESCRIPTION

[0018] A method for preparing a high-performance, high-breakdown voltage permanent ferrite includes the following specific contents:

[0019] The 5-series strontium ferrite pre-sintered material without lanthanum and cobalt, the 9-series strontium ferrite pre-sintered material with lanthanum and cobalt added, and the recycled waste are uniformly mixed in proportion as raw materials, and after adding auxiliary materials and mixing, they are put into a ball mill and fully ball milled with water, and the water is filtered after being taken out of the jar, and the permanent magnet ferrite is obtained by magnetizing and pressing in a press, and then the formed blank is heated and sintered, and then dried after grinding.

[0020] In a preferred embodiment, in the above raw materials, the addition ratio of 9 series strontium ferrite pre-sintered material is 40-50% by mass, the addition ratio of 5 series strontium ferrite pre-sintered material is 30-50% by mass, and the addition ratio of recycled waste is 10-20%.

[0021] The recycled waste is the grinding material and / or defective products produced in the preparation process of strontium ferrite. For reference, the components generally include Fe (usually in the form of iron oxide), SiO2, Al2O3, CaO, SrO, La2O3, Co3O4. The specific content of each component varies according to the recycled waste, but as long as it is the grinding material and / or defective products of strontium ferrite known in the art, it will not lead to the technical effect recorded in the present invention cannot be achieved; auxiliary materials include SiO2, SrCO3, Al2O3, H3BO3, La2O3, Co3O4 and sorbitol; the solid in the above method It is stipulated that 0.1% of sorbitol is used in the raw material weight, and the adjusted auxiliary materials include one or more of SiO2, SrCO3, Al2O3, H3BO3, La2O3 and Co3O4; further optionally, the adjustment range of the adjusted auxiliary materials is calculated as a percentage of the raw material weight, and the amount of SiO2 is 0.02-0.15%, the amount of SrCO3 is 0.3-0.8%, the amount of Al2O3 is 0.1-0.7%, the amount of H3BO3 is 0.1-0.45%, the amount of La2O3 is 1-2.25%, and the amount of Co3O4 is 0.4-0.9%.

[0022] For reference, the above raw materials can be ball-milled for 8 to 12 hours after adding auxiliary materials and mixing; in addition, a roller kiln can be used for sintering, and the sintering temperature is preferably 1210±10°C; these are well-known technologies in the art, and the present invention has no improvement on this, so they will not be repeated.

[0023] In a preferred embodiment, the breakdown voltage of the permanent ferrite prepared by the above method can reach 4-10kV, the remanence can reach more than 410mT, the coercive force can reach more than 300kA / m, the intrinsic coercive force can reach more than 360kA / m, and the maximum magnetic performance can reach 32kJ / m 3 above.

[0024] The present invention is further described below through several embodiments and comparative examples. It should be noted that the described embodiments are not all embodiments of the present invention, but only a small part thereof. Therefore, they should not be used as a decisive limitation on the protection scope of the present invention. The specific limitation should be based on the claims and the above contents.

[0025] In the following examples and comparative examples, the 5-series strontium ferrite pre-sintered material is produced from a pre-sintered material enterprise in Liaoning, and the 9-series strontium ferrite pre-sintered material is produced from a magnetic material company in Zhejiang, but these two pre-sintered materials should not be regarded as limitations of the present invention, and other pre-sintered material raw materials should also be within the scope of protection of this patent; the recycled waste used is the production waste recycled from the strontium ferrite production process of Sinosteel Tianyuan Tongli Magnetic Material Factory, and the composition is shown in Table 1 below:

[0026] Table 1 Composition of recycled waste (%)

[0027] <![CDATA[T Fe ]]> <![CDATA[SiO2]]> <![CDATA[Al2O3]]> High SrO <![CDATA[La2O3]]> <![CDATA[Co3O4]]> 61.08 0.47 0.387 1.13 9.84 1.88 0.688

[0028] Table 2 below shows the main ingredients and auxiliary ingredients of the examples and comparative examples, in units of mass percentage of the raw materials:

[0029] Table 2 Examples and Comparative Examples

[0030]

[0031]

[0032] Comparative Example 1

[0033] The 9 series pre-sintered materials and recycled waste materials were mixed evenly in a mass ratio of 78:22, and after adding the auxiliary materials in Table 2, they were placed in a ball mill for 10 hours, the materials were discharged and filtered, and the slurry was pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product was taken out, and the permanent ferrite was obtained after grinding both sides smooth and drying. The ferrite was placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties were tested. The test results are shown in Table 3.

[0034] Example 1

[0035] The 9 series pre-sintered materials, 5 series pre-sintered materials and recycled waste materials were uniformly mixed in a mass ratio of 50:30:20, and after adding the auxiliary materials in Table 2, they were put into a ball mill for 10 hours, and then the materials were discharged and filtered. The slurry was pressed into a round cake blank in a press, and then sintered in a roller kiln at a sintering temperature of 1210°C. After sintering, the ferrite sintered product was taken out, and the permanent magnet ferrite was obtained after grinding both sides smooth and drying. The ferrite was placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties were tested. The test results are shown in Table 3.

[0036] Example 2

[0037] The 9 series pre-sintered materials, 5 series pre-sintered materials and recycled waste materials were uniformly mixed in a mass ratio of 40:50:10, and after adding the auxiliary materials in Table 2, they were placed in a ball mill for 10 hours, and then the materials were discharged and filtered. The slurry was pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product was taken out, and the two sides were ground smooth and dried to obtain permanent ferrite. The ferrite was placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties were tested. The test results are shown in Table 3.

[0038] Example 3

[0039] The 9 series pre-sintered materials, 5 series pre-sintered materials and recycled waste materials were uniformly mixed in a mass ratio of 40:40:20, and after adding the auxiliary materials in Table 2, they were placed in a ball mill for 10 hours, and then the materials were discharged and filtered. The slurry was pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product was taken out, and the permanent ferrite was obtained after grinding both sides smooth and drying. The ferrite was placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties were tested. The test results are shown in Table 3.

[0040] Example 4

[0041] The 9 series pre-sintered materials, 5 series pre-sintered materials and recycled waste materials were uniformly mixed in a mass ratio of 40:40:20, and after adding the auxiliary materials in Table 2, they were placed in a ball mill for 10 hours, and then the materials were discharged and filtered. The slurry was pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product was taken out, and the permanent ferrite was obtained after grinding both sides smooth and drying. The ferrite was placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties were tested. The test results are shown in Table 3.

[0042] Example 5

[0043] The 9 series pre-sintered materials, 5 series pre-sintered materials and recycled waste materials were uniformly mixed in a mass ratio of 40:38:22, and after adding the auxiliary materials in Table 2, they were placed in a ball mill for 10 hours, and then the materials were discharged and filtered. The slurry was pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product was taken out, and the two sides were polished and dried to obtain permanent ferrite. The ferrite was placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties were tested. The test results are shown in Table 3.

[0044] Example 6

[0045] The 9 series pre-sintered materials, 5 series pre-sintered materials and recycled waste materials were uniformly mixed in a mass ratio of 40:42:18, and after adding the auxiliary materials in Table 2, they were put into a ball mill for 10 hours, and then the materials were discharged and filtered. The slurry was pressed into a round cake blank in a press, and then sintered in a roller kiln at a sintering temperature of 1210°C. After sintering, the ferrite sintered product was taken out, and the permanent ferrite was obtained after grinding both sides smooth and drying. The ferrite was placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties were tested. The test results are shown in Table 3.

[0046] Example 7

[0047] The 9 series pre-sintered materials, 5 series pre-sintered materials and recycled waste materials were uniformly mixed in a mass ratio of 40:44:16, and after adding the auxiliary materials in Table 2, they were placed in a ball mill for 10 hours, and then the materials were discharged and filtered. The slurry was pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product was taken out, and the two sides were polished and dried to obtain permanent ferrite. The ferrite was placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties were tested. The test results are shown in Table 3.

[0048] Table 3 Breakdown voltage and magnetic properties test results of the embodiments and comparative examples

[0049]

[0050] Comparative Example 1 is an original high-performance ferrite formula, which is a common product on the market. Without using the raw material and auxiliary material formula of the present invention, the breakdown voltage is below 0.03 kV, which cannot meet the demand.

[0051] After doping 30% of 5-series material in Example 1, the breakdown voltage is greatly improved compared with the control example, but the current in the ferrite is still 1mA. After continuing to increase the amount of 5-series material and reduce the amount of 9-series material, the breakdown voltage reaches more than 2kV. After adjusting the formula once, the breakdown voltage of Examples 3 and 4 reached more than 8.5kV; after adjusting the formula twice, the residual magnetism of Examples 5, 6, and 7 was increased to more than 410mT. Comparing the electrical properties and magnetic properties of Examples 1 to 7, Example 7 not only has a breakdown voltage as high as 4.4kV, but also a residual magnetism of 415.9mT, a coercive force of 306.2kA / m, an intrinsic coercive force of 366.7kA / m, and a maximum magnetic property of 33kJ / m 3 , which is consistent with the magnetic properties of the comparative example.

[0052] In addition, among the raw materials of the present invention, the 9-series strontium ferrite pre-sintered material with added lanthanum and cobalt can also be replaced with other 5-series or above high-performance ferrites with added lanthanum and cobalt, and the method of the present invention can also greatly improve the breakdown voltage of the replaced material.

[0053] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.

[0054] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for preparing a high performance and high breakdown voltage permanent ferrite, characterized in that: The specific contents include: The 5-series strontium ferrite pre-sintered material without lanthanum and cobalt, the 9-series strontium ferrite pre-sintered material with lanthanum and cobalt added, and the recycled waste are uniformly mixed in proportion as raw materials, and after adding auxiliary materials and mixing, they are put into a ball mill and fully ball milled with water, and the water is filtered after being taken out of the jar, and the permanent magnet ferrite is obtained by magnetizing and pressing in a press, and then the formed blank is heated and sintered, and then dried after grinding. Among them, the recycled waste materials are grinding materials and / or defective products generated in the preparation process of strontium ferrite, and the auxiliary materials include SiO2, SrCO3, Al2O3, H3BO3, La2O3, Co3O4 and sorbitol; in the method, sorbitol is fixedly used at 0.1% of the mass of the raw material, and the adjusted auxiliary materials include one or more of SiO2, SrCO3, Al2O3, H3BO3, La2O3 and Co3O4.

2. The method for preparing a high performance and high breakdown voltage permanent ferrite according to claim 1, characterized in that: In the raw materials, the addition ratio of 9 series strontium ferrite pre-sintered material is 40-50% by mass, the addition ratio of 5 series strontium ferrite pre-sintered material is 30-50% and the addition ratio of recycled waste material is 10-20%.

3. The method for preparing a high performance and high breakdown voltage permanent ferrite according to claim 1, characterized in that: The adjustment range of the auxiliary materials is calculated as a percentage of the raw material mass, and the amount of SiO2 is 0.02-0.15%, the amount of SrCO3 is 0.3-0.8%, the amount of Al2O3 is 0.1-0.7%, the amount of H3BO3 is 0.1-0.45%, the amount of La2O3 is 1-2.25%, and the amount of Co3O4 is 0.4-0.9%.

4. The method for preparing a high performance and high breakdown voltage permanent ferrite according to claim 1, characterized in that: The components in the recycled waste include Fe, SiO2, Al2O3, CaO, SrO, La2O3, and Co3O4.

5. The method for preparing a high performance and high breakdown voltage permanent ferrite according to claim 1, characterized in that: The raw materials are added to the auxiliary materials and mixed, and then ball milled for 8 to 12 hours.

6. The method for preparing a high performance and high breakdown voltage permanent ferrite according to claim 1, characterized in that: The sintering is carried out using a roller kiln, and the sintering temperature is 1210±10°C.

7. A method for preparing a high performance and high breakdown voltage permanent ferrite according to any one of claims 1 to 6, characterized in that: In the raw materials, the addition ratio of 9 series strontium ferrite pre-sintered material is 40%, the addition ratio of 5 series strontium ferrite pre-sintered material is 40%, and the addition ratio of recycled waste material is 20%. In the auxiliary materials, the amount of SiO2 is 0.08-0.14%, the amount of SrCO3 is 0.7-0.8%, the amount of Al2O3 is 0.1-0.3%, the amount of H3BO3 is 0.3-0.4%, the amount of La2O3 is 2.25%, and the amount of cobalt oxide is 0.9%. The permanent ferrite prepared by the method has a breakdown voltage of 4-10kV, a remanence of more than 410mT, a coercive force of more than 300kA / m, an intrinsic coercive force of more than 360kA / m, and a maximum magnetic performance of 32kJ / m 3 above.

Citation Information

Patent Citations

  • High-performance permanent ferrite and dyadic manufacturing method thereof

    CN101409122A

  • Preparation method for recycling of permanent magnetic ferrite waste

    CN103102150A

Cited By

  • Preparation method of permanent magnetic ferrite with high remanence and high resistance

    CN120817796A